Empyema necessitans secondary to tuberculosis: a case report - Kumar, Anil; Mohammad Azmi, Mohd Azem Fathi; Jasmani, Asraf Haslam; Wan Mokhter, Wan Mokhzani (Universiti Putra Malaysia, 2022)
Empyema necessitans (EN) is a sporadic disease in the 21st century. It is a condition where the empyema has diffused and is loculated in the extrapleural space. It is usually caused by Tuberculosis (TB) infection or immunocompromised condition. Its manifestation, which is often vague in the beginning, leads to diagnostic dilemmas and delays in management. This has considerably affected patients adversely and incurred avoidable healthcare costs. We describe a rare case of empyema necessitans secondary to pulmonary tuberculosis in a 43-year-old male who presented to the emergency department with right anterior chest wall swelling, which was associated with pain, lethargy, malaise and significant loss of weight. Targeted ultrasonography of the anterior chest wall revealed a right anterior chest wall collection with intrathoracic extension. Contrast-enhanced computed tomography of the chest showed a multiloculated right chest wall collection with intrathoracic extension. Percutaneous drainage of the collection was performed, and the pus sent for Mycobacterium tuberculosis culture was positive. This case highlights the importance of a high index of suspicion and clinical awareness for this dangerous and silent disease.